Feasibility Test of Dermatoglyphic Practicum Guide Based on Guided Inquiry - Gusti Ayu Muthia; Jodion Siburian; Evita Anggereini (Magister Pendidikan Biologi, Universitas Negeri Medan, 2022)
One of the lessons contained in the genetics practicum is dermatoglyphics. During the genetic practicum on dermatoglyphic material, students experienced few difficulties in explaining the material. Therefore, a genetic practicum guide for dermatoglyphic material was developed. This study aims to produce an appropriate guided inquiry-based practicum guide from the aspect of the feasibility of the material and media. The results of this study are expected to provide new innovations as a source of learning for students. The development of the practical guide is carried out using the ADDIE model. This study reviews the development stage at the ADDIE stage. The data analysis carried out was descriptive qualitative and descriptive quantitative. Qualitative data came from the validator's suggestion while quantitative data was obtained from a Likert questionnaire on a scale of 1-5. The research instrument is a material expert validation sheet and media expert. Based on the research, the average results of stage 1 material validation were 56.63% with a fairly good category and stage 2 validation was 71.60%. While the results of the media validation stage 1 obtained 34.78% with a fairly good category, validation stage 2 66.19% good category, and validation stage 3 has a very good category with a percentage of 89.05%. The material and media validation process is carried out in stages and improvements are made so that it can be concluded that this practical guide is feasible.